Prioritizing problems in and solutions to homecare safety of people with dementia: supporting carers, streamlining care. Issue 1 (December 2017) - Tudor Car, Lorainne; El-Khatib, Mona; Perneczky, Robert; Papachristou, Nikolaos; Atun, Rifat; Rudan, Igor; Car, Josip; Vincent, Charles; Majeed, Azeem
Abstract Background Dementia care is predominantly provided by carers in home settings. We aimed to identify the priorities for homecare safety of people with dementia according to dementia health and social care professionals using a novel priority-setting method. Methods The project steering group determined the scope, the context and the criteria for prioritization. We then invited 185 North-West London clinicians via an open-ended questionnaire to identify three main problems and solutions relating to homecare safety of people with dementia. 76 clinicians submitted their suggestions which were thematically synthesized into a composite list of 27 distinct problems and 30 solutions. A group of 49 clinicians arbitrarily selected from the initial cohort ranked the composite list of suggestions using predetermined criteria. Results Inadequate education of carers of people with dementia (both family and professional) is seen as a key problem that needs addressing in addition to challenges of self-neglect, social isolation, medication nonadherence. Seven out of top 10 problems related to patients and/or carers signalling clearly where help and support are needed. The top ranked solutions focused on involvement and education of family carers, their supervision and continuing support. Several suggestions highlighted a need for improvement of recruitment, oversight and working conditions of professional carers and for different home safety-proofing strategies. Conclusions Clinicians identified a range of suggestions for improving homecare safety of people with dementia. Better equipping carers was seen as fundamental for ensuring homecare safety. Many of the identified suggestions are highly challenging and not easily changeable, yet there are also many that are feasible, affordable and could contribute to substantial improvements to dementia homecare safety.